Early initiation of gonadotropin-releasing hormone antagonist versus long agonist protocols in polycystic ovary syndrome patients undergoing intracytoplasmic sperm injection cycles. Issue 2 (May 2016) - Youssef, Hamed; Thabet, Mahmoud; Emam, Mohamed; El Azab, Said; Al-Inany, Hesham
Abstract : Purpose: The aim of this study was to compare the efficacy and safety of early initiation of gonadotropin-releasing hormone (GnRH) antagonist and long GnRH agonist protocol in oral contraceptive-pretreated polycystic ovary syndrome (PCOS) patients undergoing intracytoplasmic sperm injection (ICSI) cycles. Design: The study design was a randomized controlled one. Setting: The study was conducted in the tertiary university fertility care unit Materials and methods: Seventy infertile PCOS patients under the age of 35 years coming for the first ICSI trial from January 2012 to December 2014 were randomly allocated to an ovarian stimulation protocol consisting of either GnRH agonist long protocol (control group A) or early initiation of GnRH antagonist (study group B) after pretreatment with oral contraceptive pill. Ovulation was triggered with human chorionic gonadotropin when at least three mature follicles measuring 17 mm were detected. Main outcome measures: The primary outcome included number of gonadotrophin ampoules used per each cycle, days of stimulation, number and degree of maturity of retrieved oocytes, rate of fertilization, and available embryo for transfer. The secondary outcome measures were implantation rate and incidence of ovarian hyperstimulation syndrome (OHSS). Results: Both days of stimulation and number of ampoules of human menopausal gonadotropin were statistically significantly greater in group A than in group B (11.25±1.69 vs. 9.48±0.83, P <0.001 and 32.46±7.34 vs. 26.59± 2.67, P <0.001, respectively). Serum E2 level on the day of human chorionic gonadotropin administration was statistically significantly lower in group B than that in the group A (2441.55±493.30 and 3012.57±845.31, respectively, P =0.003). Fertilization rate and the number of grade A embryos were higher in group B compared with group A, and this difference was statistically significant (87.89 vs. 77.49%, P =0.004 and 6.38±2.31 vs. 4.57±2.17, P =0.004, respectively). No cases of severe OHSS were documented in both groups. However, moderate OHSS was documented in four cycles of group A but was not documented in any cycle of group B; this difference was statistically significant. Conclusion: This novel antagonist protocol may be a safe and efficient treatment for PCOS patients undergoing ICSI cycles with comparable results to the standard long GnRH agonist protocol.